Porosity Value Analysis of Limestone as a Groundwater Reservoir in West Kaidundu Village, Bulawa Sub-District, Bone Bolango Regency - Mooduto, Tirsya Aygina Jaenet; Permana, Aang Panji; Hutagalung, Ronal (Universitas Negeri Gorontalo, 2025)
West Kaidundu is a village with diverse terrain conditions, covering high hilly areas, some lowlands, and coastal areas in Bulawa Sub-District, Bone Bolango Regency. The diverse morphological and geological conditions have an impact on the potential of natural resources, the distribution of limestone, and different geological structures.Research on the porosity of limestone is crucial to obtain information about its porosity value. A study analyzing the porosity of limestone in Kaidundu Barat Village has not been conducted before. Therefore, this research is significant and interesting to carry out at the study location. The results of the study reveal the geological conditions of the research area, which consists of three geomorphological units: pyroclastic ridge, karst plain, and alluvial plain units. The study area is composed of wackestone and mudstone limestone, pyroclastic breccia, and alluvial deposits. From the porosity analysis, the wackestone limestone in the study area, categorized as reservoir rock, falls into the poor category, while the mudstone limestone is classified as fair.